2023
DOI: 10.21037/tp-22-361
|View full text |Cite
|
Sign up to set email alerts
|

The management of pectus excavatum in pediatric patients: a narrative review

Abstract: Background and Objective: Pectus excavatum is the most common congenital chest wall anomaly, the hallmark of which is the caved-in appearance of the anterior chest. A growing body of literature exists surrounding methods of surgical correction, though considerable variability in management remains. The primary objectives of this review are to outline the current practices surrounding the care of pediatric patients with pectus excavatum and present emerging trends in the field that continue to impact the care o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…Among the complications of PE orthopedic surgery, the most troublesome problem for surgeons is the postoperative rejection of the inserted plate [13] . Mild to moderate rejection can lead to incision infection, non-healing incision, and delayed postoperative hospitalization, which not only increases the psychological burden of patients, but also greatly affects the therapeutic effect of surgery and postoperative quality of life, and some patients with delayed incision healing will have scarring of the skin tissue after recovery [6,13,17] . Patients with moderate to severe rejection can suffer from serious complications such as chest infection and eventually early removal of the placed plate leading to orthopaedic failure.…”
Section: Discussionmentioning
confidence: 99%
“…Among the complications of PE orthopedic surgery, the most troublesome problem for surgeons is the postoperative rejection of the inserted plate [13] . Mild to moderate rejection can lead to incision infection, non-healing incision, and delayed postoperative hospitalization, which not only increases the psychological burden of patients, but also greatly affects the therapeutic effect of surgery and postoperative quality of life, and some patients with delayed incision healing will have scarring of the skin tissue after recovery [6,13,17] . Patients with moderate to severe rejection can suffer from serious complications such as chest infection and eventually early removal of the placed plate leading to orthopaedic failure.…”
Section: Discussionmentioning
confidence: 99%
“…PE occurs in about 1 out of every 400 individuals ( 36 ). Studies have reported that patients with PE suffer from body image dissatisfaction and thus avoid social situations ( 37 - 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ESP 'single shot' blockade has the beneficial effect of reducing the amount of opioids needed. It resulted in a reduction in the total dose of opioids and the occurrence of adverse effects after pharmacotherapy [30,31]. Cryoablation performed together with the 'single shot' ESP blockade is therefore a safer option compared to keeping the catheter to continue regional analgesia for several days.…”
Section: Discussionmentioning
confidence: 99%